The Effect of Religiosity on Customer Trust on Brand Loyalty to McDonalds in Generation Z After the Israeli-Palestinian Conflict - Dian Anggraeni; Nilta Rosada; Andin Kamila; Adi Setiawan; Tiara Muthiarsih (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The purpose of this study is to examine the effect of religiosity and customer trust on brand loyalty among Generation Z (Muslim consumers in Indonesia), during a particular timeframe (post-Israeli-Palestinian conflict), thereby adding nuanced insights to consumer behavior research in a globalized context. The study is located in Cirebon, Indonesia, with research subjects namely consumers who buy products from McDonald's and people who follow the issue of boycotting Israeli products from the Palestinian conflict among FEB Management students of Universitas Swadaya Gunung Jati. The results of the fit model test show that religious values and consumer trust significantly impact McDonald''s brand loyalty in the Z generation. Consumer trust has a positive and significant effect on Brand loyalty (Z), with the remaining (1 - 0.505) = 0.495 (49.5%), which is influenced by other variables not determined by the model. This research contributes by bridging the gap between religious values, consumer trust, and brand loyalty, in the post-israeli conflict Z generation (Generation Z, Muslims in Indonesia). The study suggests strengthening the involvement of consumers through social media and promotional events, while also considering the importance of religious beliefs in decision-making.